Quality of consumer-oriented websites containing information about the second trimester ultrasound examination during pregnancy - Susanne Georgsson; Tommy Carlsson (BMC, 2020)
Abstract Background Providing information about prenatal tests is a clinical challenge and the public frequently accesses the Web to read pregnancy-related information. The overarching aim of this study was to investigate the quality of consumer-oriented websites addressing obstetric ultrasound examination in the second trimester of pregnancy. Methods Swedish websites were identified with Google, using 20 search strings and screening 400 hits (n = 71 included websites). Reliability and information about the examination were assessed with the DISCERN instrument, completeness was assessed according to national guidelines, and readability analyzed with the Readability Index. Popularity was determined with the ALEXA tool and search rank was determined according to Google hit lists. Results The mean total DISCERN score was 29.7/80 (SD 11.4), with > 50% having low quality for 15 of the 16 questions. The mean completeness score was 6.8/24 (SD 4.5). The Readability Index ranged between 22 and 63, with a mean of 42.7 (SD 6.8), indicating difficult readability. Weak and non-significant correlations were observed between ALEXA/search rank and the investigated quality variables, except for search rank and reliability. Conclusions The quality of consumer-oriented websites addressing the second trimester ultrasound examination is low. Health professionals need to discuss this with expectant parents considering undergoing the examination. There is a need for efforts that aim to improve the poor quality of online sources in the field of prenatal examinations.